Short circuit current analysis of DFIG wind turbines with crowbar protection - Zhou, H.L.; Yang, G.; Li, D.Y. (2009 International Conference on Electrical Machines and Systems : 15-18 November 2009, 2009)
For DFIG (doubly fed induction generator)-based wind turbines, crowbar is a commonly used protection method against surge current caused by sudden drop of the grid voltage during the period of LVRT (low voltage ride-through). Based on detailed analysis of the transient flux characteristics of DFIG with the crowbar fired, a simplified model is proposed to analyze and approximate the short circuit current accurately. Meanwhile the maximum short circuit current and the LVRT capability are evaluated. After that the dc-link voltage clamp effect is pointed out and a crowbar design method based on the dc-link voltage is proposed accordingly. A typical 1.5 MW DFIG wind turbine is used for case study. The analysis and simulation results show that, when the crowbar resistance is small or the fault is not severe, the dc-link clamp effect does not occur so the simplified model can give a satisfactory approximation of the short circuit current; otherwise, the dc-link clamp effect must be taken into account in determining the short circuit current. In this case, it is found that excessive high crowbar resistance will not improve the LVRT capability substantially, but put more stress on the fly-wheel diodes of the rotor side converter.